2013
DOI: 10.1016/j.jns.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

VZV multifocal vasculopathy with ischemic optic neuropathy, acute retinal necrosis and temporal artery infection in the absence of zoster rash

Abstract: We describe a 54-year-old diabetic woman who developed ischemic optic neuropathy followed by acute retinal necrosis and multiple areas of focal venous beading. Vitreous fluid contained amplifiable VZV DNA but not HSV-1, CMV or toxoplasma DNA. The clinical presentation was remarkable for jaw claudication and intermittent scalp pain, prompting a temporal artery biopsy that was pathologically negative for giant cell arteritis, but notable for VZV antigen. The current case adds to the clinical spectrum of multifoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
(16 reference statements)
1
28
1
Order By: Relevance
“…Recent reports have revealed a striking association between VZV and TA infection, including: a case of multifocal VZV vasculopathy manifested by ION and TA infection that developed one month after ipsilateral ophthalmic-distribution zoster [4]; 2 additional cases of multifocal VZV vasculopathy manifested by ION and TA infection with no history of zoster [5, 6]; and the detection of VZV antigen and DNA in archived material from 5 subjects, all of whom had ION, in analysis of 24 GCA-negative TAs [7], indicating that VZV multifocal vasculopathy can present with the full spectrum of clinical features and laboratory abnormalities seen in GCA and suggesting that VZV might actually cause GCA. More compelling evidence linking VZV to GCA came from analysis of a TA that was GCA-negative pathologically, but contained multiple skip areas with VZV antigen; additional pathological analysis of sections adjacent to those containing VZV antigen revealed the classic pathological changes of GCA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed a striking association between VZV and TA infection, including: a case of multifocal VZV vasculopathy manifested by ION and TA infection that developed one month after ipsilateral ophthalmic-distribution zoster [4]; 2 additional cases of multifocal VZV vasculopathy manifested by ION and TA infection with no history of zoster [5, 6]; and the detection of VZV antigen and DNA in archived material from 5 subjects, all of whom had ION, in analysis of 24 GCA-negative TAs [7], indicating that VZV multifocal vasculopathy can present with the full spectrum of clinical features and laboratory abnormalities seen in GCA and suggesting that VZV might actually cause GCA. More compelling evidence linking VZV to GCA came from analysis of a TA that was GCA-negative pathologically, but contained multiple skip areas with VZV antigen; additional pathological analysis of sections adjacent to those containing VZV antigen revealed the classic pathological changes of GCA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Given the similar clinical and pathological features seen in VZV vasculopathy and giant cell arteritis (GCA), it has been postulated that there may be a role of VZV in the pathogenesis of GCA [15][16][17][18]. The study by Gilden et al [19] has shown the presence of VZV antigen in 74% patients of temporal artery biopsy-proven GCA versus 8% in normal temporal arteries (p<0.0001), while Nagel et al [20] found the proportions to be 64% and 22% respectively (p<0.001).…”
Section: Vzv Vasculopathy and Giant Cell Arteritismentioning
confidence: 99%
“…Multifocal temporal arteritis is another possible presentation of VZV vasculopathy. Termed multifocal VZV vasculopathy, it presents with the same clinical signs, symptoms, and laboratory findings as giant cells arteritis (GCA) and should be considered in cases of classic GCA where the temporal artery biopsy is negative (49) . Prompt diagnosis of VZV vasculopathy is imperative not only because it is a life-threatening condition with a mortality rate of 25% (50) if left untreated but also because the prognosis is benign when treated with intravenous acyclovir (51) .…”
Section: Hzo and Vasculopathy: Risk Analysismentioning
confidence: 99%